1985
DOI: 10.1111/j.1348-0421.1985.tb00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Patterns of Extracellular Deoxyribonuclease (DNase) and Their Correlation with T‐Type in Group A Streptococci

Abstract: Molecular heterogeneity of the extracellular deoxyribonuclease (DNase) in group A streptococci was demonstrated in 42 clinical isolates. Although polyacrylamide gel electrophoretic patterns of the extracellular DNase of all the isolates were heterogeneous, they could be divided into five main patterns with respect to the presence or absence of three DNase components including DNase B. By comparing the electrophoretic patterns of DNase in all the isolates with their T-types, we found that the patterns were quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Hence, we designated Spy0747 as SpnA (S. pyogenes nuclease A). All S. pyogenes strains express one or more DNase genes (Wannamaker, 1958;Miyakawa et al, 1985;Ferreira et al, 1992), and recent genome studies have revealed that all S. pyogenes strains analysed contain several genes presumed to encode extracellular DNases. Extracellular streptococcal DNases have been considered as virulence factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we designated Spy0747 as SpnA (S. pyogenes nuclease A). All S. pyogenes strains express one or more DNase genes (Wannamaker, 1958;Miyakawa et al, 1985;Ferreira et al, 1992), and recent genome studies have revealed that all S. pyogenes strains analysed contain several genes presumed to encode extracellular DNases. Extracellular streptococcal DNases have been considered as virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include M protein, streptococcal inhibitor of complement, streptococcal pyrogenic toxins, haemolysins, and several DNases (Cunningham, 2000). DNases have been extensively characterized (McCarty, 1949;Miyakawa et al, 1985;Ferreira et al, 1992). However, there was no direct evidence that DNases are virulence factors, until Sumby et al (2005a) provided such evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Many indirect lines of evidence implicate DNases in GAS pathogenesis. First, all GAS strains produce at least one DNase, and most strains make several distinct enzymes (13,(15)(16)(17). Second, expression of DNase is up-regulated upon interaction of GAS with human epithelial cells, polymorphonuclear leukocytes (PMNs), and oropharynx (20,21,24,25).…”
mentioning
confidence: 99%
“…These factors include capsule, M protein, streptococcal inhibitor of complement, streptococcal pyrogenic toxin superantigens, hemolysins, and several DNases (8 -11). DNases were among the first secreted GAS proteins to be identified and extensively characterized (6,(12)(13)(14)(15)(16)(17). However, after almost 60 years of investigation, there is no direct evidence that DNases are virulence factors (18 -23).…”
mentioning
confidence: 99%
“…S. pyogenes strains commonly express DNase B, but the other three DNases are not frequently expressed and thus DNase B has a major share of total DNase activity in most strains (5,7,8). Determination of antibody titers to DNase B has been used to confirm a clinical diagnosis of a previous S. pyogenes infection and the level of anti-DNase B antibody in invasive cases was significantly lower than those in healthy individuals (1).…”
mentioning
confidence: 99%